(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article aims at reflecting on some critical issues emerging from the observation of the 40 years long implementation of the law 833/1978, looking at them as a result of the complex process of turning constitutional social rights, from lex (duties and aims of the state) into iura (real individual rights). Different topics are taken into account: the shifting of decision-making process from parliament to government and from politics to technology; the possibility to ensure equity and democratic quality in the relationship between needs and resources; the original quality of participatory previsions as means of a patient’s active responsibility in his/her relationship with the doctor; the constitutional foundation of self-determination in the relationship between the doctor and the patient, facing the physician’s conscientious objection.